Analysis of the 90º and 150º angles for increment counting in otoliths of estuarine catfish - Igor Souza de Morais; Juliana de Souza Azevedo (Ocean and Coastal Research)
Fish age can be estimated with the use of age rings in calcified structures, such as otoliths. However, it is important to select an appropriate axis for counting the number of increments and to confirm that the age rings are visible in the otolith and interpreted correctly. In this study, the distance between consecutive age rings in the lapillus otoliths of Cathorops spixii and Genidens genidens catfish from the Cananéia-Iguape Estuarine– Lagoon Complex was measured along otoliths at predetermined 90° and 150° axes. In general, the number of increments observed per otolith ranged from 1 to 14 for both species. The positive linear relationship between the total length of the fish and the radius of the age rings suggests that otolith size is a reliable somatic proxy of C. spixii (=0.872) and G. genidens (=0.896). The axes chosen to measure the distances of each increment were proven accurate, especially the straight axis. Our study indicates that the 90º and 150º angles can be used for increment counting, but caution is required for otoliths with the same growth morphology: potentially confusing increments are more prevalent along the 150º axis, and this may hinder increment analysis of G. genidens and C. spixii. Therefore, the 90º axis provides better visualization of the closest opaque and translucent zones and should be prioritized for increment counting in the C. spixii and G. genidens ariids.